Do Orthodontists and Orthodontic Residents Perceive that Work-Life Balance and Work-Family Conflicts Affect Their Organizational Commitment? - Yemitan, Tolulase Abosede; Adeyemi, Tope Emmanuel (European Dental Research and Biomaterials Journal, 2021)
Objectives Two of lives’ most important domains may be in conflict with each other. This study investigated the association between perceived work-life balance (WLB), work interference with family (WIF), family interference with work (FIW), and organizational commitment (OC) of Nigerian orthodontists and orthodontic residents.Materials and Methods Consultant orthodontists (n = 37) as well as orthodontics residents (n = 33) responded to an electronic questionnaire.Statistical Analysis Multivariate analysis of variance assessed significant differences among demographic and career features on WLB, WIF, and FIW. Spearman’s correlation coefficient and then multiple regression analysis examined relationships among perception of WLB, WIF, FIW, and OC.Results Perceived WLB and WIF had statistically significant negative correlation with OC among Nigerian orthodontic practitioners. However, the study finds a positive, but not statistically significant correlation of perception of FIW and OC.Conclusion Perceived WLB and WIF are significant contributors to levels of OC among Nigerian orthodontists and orthodontic residents. Multiple regression analysis identified a model that includes perceived WLB, WIF, and FIW that accounts for 16.7% of the variation in OC.
Keywords: health careers; family issues; gender; overcoming job stress; orthodontics